First observation and study of the K± → π±π0e+e− decay with the NA48/2 experiment at CERN. (April 2020) - Bloch-Devaux, B
Abstract: The first observation of the rare decay K ± → π ± π 0 e + e − is reported by the NA48/2 experiment at CERN, based on 4919 candidates with 4.9% background contamination. From the analysis of 1.7 × 10 11 kaon decays collected in 2003–2004, the branching ratio in the full kinematic region is measured to be BR( K ± → π ± π 0 e + e − )= (4.24 ± 0.14) × 10 −6 . A detailed study of the kinematic space shows evidence for a structure dependent contribution. Both measured BR and structure dependent contribution are in perfect agreement with theoretical predictions based on Chiral Perturbation Theory. Several P- and CP-violating asymmetries are also evaluated.